Enhancing Students’ Understanding of Integrated Social Sciences through Contextual Learning Model at MTSS Sungai Rambah - Aldery Safriadii; Ubaidillah Fuad (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to improve students’ understanding of Integrated Social Sciences (SKI) at MTSS Sungai Rambah through the application of the Contextual Learning Model. SKI is a crucial subject that integrates aspects of history, geography, and social studies, encouraging students to understand the interconnection between these disciplines and their relevance to real-life situations. Traditional teaching methods have often failed to fully engage students or demonstrate the practical application of the subject matter. The Contextual Learning Model, which focuses on relating academic content to students’ real-world experiences, offers an effective solution to address these issues. The research was conducted with a group of students at MTSS Sungai Rambah during the 2024 academic year. This study follows a cyclical process of planning, action, observation, and reflection. Data were collected through pre- and post-test assessments, classroom observations, and interviews with students and teachers. The objective was to determine how the Contextual Learning Model could enhance students’ engagement, critical thinking, and understanding of SKI concepts. The results indicated that the Contextual Learning Model significantly improved students’ understanding of SKI. Students became more actively engaged in discussions, demonstrated improved problem-solving skills, and were able to relate historical and geographical content to contemporary issues. Furthermore, the model encouraged collaboration and communication among students, fostering a deeper understanding of the subject matter. In conclusion, the implementation of the Contextual Learning Model at MTSS Sungai Rambah proved to be an effective approach in enhancing students’ understanding of Integrated Social Sciences. The study suggests that this model should be further integrated into teaching strategies to promote active learning and critical thinking.